Tourists' Perceptions of Tourism Destination Attributes at Tanjung Aan Beach, Central Lombok Regency - Abdul Muhaimin; M. Setyo Nugroho; Wahyu Khalik (Jurnal Pariwisata Nusantara (JUWITA), 2023)
Purpose: The objective of this research endeavor is to ascertain the level of tourist satisfaction and perception regarding the characteristics of tourist destinations situated on Tanjung Aan Beach, Central Lombok Regency. Method: This research employs a qualitative approach to descriptive research. The data collection methodology comprises three stages. Initially, observers were conducted at Tanjung Aan Beach in Central Lombok. The second step was to conduct structured interviews with thirty tourists, ten of whom were locals, ten of whom were foreigners, and ten of whom were domestic. Third, documentation studies derived from pertinent literature to the subject of study. Result: The findings of this research suggest that there are variations in the perceptions of foreign, domestic, and local tourists who visit the tourist destinations of Tanjung Aan Beach in Central Lombok. Tourists hold favorable perceptions of Tanjung Aan Beach in regard to its culinary offerings, souvenir center, parking area facilities, surfing facilities and services, boat and canoe rental services, road accessibility, and prices. Tourists generally hold negative perceptions of amenities such as prayer rooms, restrooms, trash cans, and relaxing areas like gazebos and beach chairs. According to the findings of the interview, a total of 26 tourists expressed satisfaction with the destination attributes of Tanjung Aan Beach, while 4 tourists indicated dissatisfaction. Contribution: This study enhances our understanding of how tourists perceive the characteristics of the Tanjung Aan Beach in Central Lombok as a destination. The findings of this research provide policymakers and implementers with suggestions for enhancing the qualities of tourist destinations and meeting the needs of tourists.